2018
DOI: 10.3390/w10050589
|View full text |Cite
|
Sign up to set email alerts
|

Fast Simulation of Large-Scale Floods Based on GPU Parallel Computing

Abstract: Abstract:Computing speed is a significant issue of large-scale flood simulations for real-time response to disaster prevention and mitigation. Even today, most of the large-scale flood simulations are generally run on supercomputers due to the massive amounts of data and computations necessary. In this work, a two-dimensional shallow water model based on an unstructured Godunov-type finite volume scheme was proposed for flood simulation. To realize a fast simulation of large-scale floods on a personal computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Several examples of solvers based on shallow water equations on GPU are in [98,[122][123][124][125][126]. These allow for large-scale flood simulations to be performed using only one GPU.…”
Section: High Performance Computing Solutions For Complex Hydraulic Ementioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of solvers based on shallow water equations on GPU are in [98,[122][123][124][125][126]. These allow for large-scale flood simulations to be performed using only one GPU.…”
Section: High Performance Computing Solutions For Complex Hydraulic Ementioning
confidence: 99%
“…That new version of IBER solved 24 h of an extreme flash flood in less than 10 min. The work in [126] presented a shallow water model based on the finite volume approach implemented for GPU with the OpenACC language [128]. OpenACC allows GPU parallelization to be implemented automatically using compiler directives like OpenMP for CPUs.…”
Section: High Performance Computing Solutions For Complex Hydraulic Ementioning
confidence: 99%
“…The experiments show a significant improvement in computational efficiency that opens up the possibility of using their solution for real-time forecasting of flood events as well. Liu et al [13] proposed parallel OpenACC implementation of the two-dimensional shallow water model for flood simulation. The results of their experiments demonstrated achievements of up to one order of magnitude in speedup in comparison with the serial solution.…”
Section: Remote Sensing and Dta Algorithms Implementation On A Gpumentioning
confidence: 99%
“…In recent years, many one-and two-dimensional (1D, 2D) numerical models have been developed and applied to the investigation of river and urban floods [4][5][6][7][8][9][10][11][12][13][14]. For the 1D numerical model, Tomasz et al [12] carried out an assessment of the impact of bridges on flood flow of the Warta River near Wronki in Poland using the HEC-RAS software package.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of the LiDAR and Graphics processing units (GPUs) techniques, 2D numerical models have been extensively investigated and applied to flood inundation [20,21]. Very accurate, inexpensive DEM data has been obtained easily by LiDAR, and the GPU technique significantly improved the computational efficiency of the numerical model and maked available very accurate numerical methods [10,22]. Meesuk et al [23] demonstrated the accuracy of LiDAR data for a numerical flood model.…”
Section: Introductionmentioning
confidence: 99%